Neurological complications associated with influenza in hospitalized children. Issue 1 (13th December 2022) - Jantarabenjakul, Watsamon; Paprad, Tanitnun; Paprad, Tunchanok; Anugulruengkitt, Suvaporn; Pancharoen, Chitsanu; Puthanakit, Thanyawee; Chomtho, Krisnachai
Abstract: Background: Influenza is a known respiratory and potential neurotropic virus. This study aimed to determine the prevalence and outcomes of influenza‐related neurological complications among hospitalized children. Methods: All medical records of hospitalized children aged <18 years old diagnosed with influenza at a tertiary care hospital in Bangkok were retrospectively reviewed. Influenza infection was confirmed by rapid antigen or reverse transcription polymerase chain reaction tests. Neurological characteristics and clinical outcomes were analyzed using the Pediatric Cerebral Performance Category Scale. Results: From 2013 to 2018, 397 hospitalized children with a median age of 3.7 years (interquartile range [IQR]: 1.6–6.9) were included. The prevalence of neurological complications, including seizure or acute encephalopathy, was 16.9% (95% confidence interval [CI]: 13.3–20.9). Influenza A and B were identified in 73.1% and 26.9% of the patients, respectively. Among 39 (58.2%) acute symptomatic seizure cases, 25 (37.3%) children had simple febrile seizures, 7 (10.4%) had repetitive seizures, and 7 (10.4%) had provoked seizures with pre‐existing epilepsy. For 28 (41.8%) encephalopathy cases, the clinical courses were benign in 20 (29.9%) cases and severe in 8 (11.9%) cases. Ten (14.9%) children needed intensive care monitoring, and 62 (93.5%) fully recovered to their baselines at hospital discharge. Predisposing factors to the neurological complications included a history of febrile seizure (adjusted odds ratio [aOR]: 20.3; 95% CI: 6.6–63.0), pre‐existing epilepsy (aOR: 3.6; 95% CI: 1.3–10.2), and a history of other neurological disorders (aOR: 3.5; 95% CI: 1.2–10.2). Conclusions: One fifth of hospitalized children with influenza had neurological complications with a favorable outcome. Children with pre‐existing neurological conditions were at higher risk for developing neurological complications.